Preparation of asphalt emulsions in the laboratory - Ulloa Calderón, Andrea (2014)
Costa Rica has used asphalt emulsions for different purposes quite extensively over the years. Nevertheless, asphalt emulsion preparation and its storage care needs have been overlooked by users who employ these emulsions on a regular basis. This article intends to provide details about the procedures involved in different asphalt emulsion lab preparation. In addition, the article also gives a series of recommendations about how to properly handle these emulsions during and after the manufacturing process so that the specific desired application outcome can be achieved.